A prospective, randomized, blinded, placebo-controlled multisite clinical study of bedinvetmab, a canine monoclonal antibody targeting nerve growth factor, in dogs with osteoarthritis. (November 2021) - Corral, Maria J.; Moyaert, Hilde; Fernandes, Tiago; Escalada, Monica; Kira S Tena, Jezaniah; Walters, Rodney R.; Stegemann, Michael R.
Abstract: Objective: Bedinvetmab is a canine monoclonal antibody targeting nerve growth factor. This study evaluated the efficacy and safety of bedinvetmab for alleviation of pain associated with osteoarthritis in dogs. Study design: Double- blind, randomized, multicentre, placebo-controlled study. Animals: Client-owned dogs ( n = 287) with osteoarthritis. Methods: Dogs were randomized (1:1) to subcutaneous injection with placebo (saline, n = 146) or bedinvetmab (0.5–1.0 mg kg –1, n = 141) administered monthly. After 3 months, 89 bedinvetmab-treated dogs that responded positively based on owner and veterinarian assessments were administered up to six additional doses of bedinvetmab in a single-armed open-label continuation phase. The primary efficacy end point was treatment success based on the owner-assessed canine brief pain inventory (CBPI) on day 28. Treatment success was defined as ≥ 1 reduction in pain severity score (0–10) and ≥ 2 in pain interference score (0–10). Results: Percentage treatment success was significantly greater in the bedinvetmab group than in the placebo group from day 7 through all assessed time points ( p ≤ 0.0025). On day 28, 43.5% of dogs achieved treatment success with bedinvetmab compared with placebo (16.9%) ( p = 0.0017). Treatment success continued through days 56 (50.8%) and 84 (48.2%) in the bedinvetmab group and was < 25% in the placebo group at all time points. Sustained efficacy was demonstrated in the continuation phase. Adverse health events occurred at similar frequencies in both groups. They were considered typical for a population of dogs with osteoarthritis and not related to study treatment. Treatment with bedinvetmab demonstrated a significant effect on all three components of CBPI—pain interference, pain severity, quality of life. Conclusions and clinical relevance: This study demonstrated the effectiveness and safety of bedinvetmab administered monthly for up to 9 months at 0.5–1.0 mg kg –1 for alleviation of pain associated with canine osteoarthritis.